Consolidation characteristics of stiff Nong Ngoo Hao clay - Chana Towan; Balasubramaniam, A.S.; Moh, Za-Chieh; Brenner, R.P.; Holmberg, Soren; The government of Canada (Bangkok : Asian Institute of Technology, 1976)
This thesis presents a study on consolidation of clays. In the study undisturbed Stiff Nong Ngoo Hao Clay were subjected to varying consolidation pressures, pressure increment ratios and pressure increment durations during one-dimensional consolidation. The data by the previous investigators on Weathered clay and Soft clay were included for comparison purpose. The test results were interpreted by using Terzaghi and Gibson & La 's theory. It is found that the effects of loading conditions on compressibility were insignificant, however, the rate of pore water pressure dissipation was much faster than that predicted by the theories of Terzaghi and Davis & Raymond. The rate of consolidation was found to be a function of loading conditions.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1976
Keywords: Clay -- Thailand -- Nong Ngoo Hao -- Testing